MAXILLOFACIAL INJURIES IN COMBAT SPORTS: PREVALANCE AND PREVENTION – A LITERATURE REVIEW - Zuzanna Krupa; Julia Skowrońska-Borsuk; Martyna Narożniak; Adrianna Ewa Pękacka; Bartłomiej Czerwiec; Adam Borsuk; Joanna Katarzyna Pergoł; Malwina Wojtas; Julia Borkowska; Julia Sposób (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and Purpose: An increasing number of individuals are engaging in combat sports. Although these activities offer numerous health benefits, they also carry a significant risk of maxillofacial injuries. Such injuries may include facial bone fractures, dental trauma, soft tissue damage, as well as injuries to the nose and eyes. There are effective methods to reduce this risk, such as the use of mouthguards, helmets, and face masks. However, awareness regarding the use of this protective equipment remains low, and there are no formal requirements mandating their use. The aim of this study is to compare the prevalence of different types of maxillofacial injuries in combat sports and to explore strategies for their prevention. Materials and Methods: The review is based on throughout analysis of the materials selected from PubMed, Scopus and Google Scholar using following keywords: maxillofacial trauma, maxillofacial injury, combat sports, martial arts, orofacial injury, dental trauma, dental injury, mouthguards, helmets, facemasks Conclusions: Research shows that the level of awareness regarding the prevention of maxillofacial injuries is low among both athletes and coaches. This highlights the importance of increasing education and awareness in this area. Furthermore, there is a clear need for additional long- term randomized controlled trials to investigate the incidence and characteristics of these injuries, which would contribute to the development of evidence-based prevention strategies.